RESILIENSI ANAK TUNGGAL YANG MEMILIKI ORANGTUA TUNGGAL DENGAN STATUS SOSIAL EKONOMI RENDAH - Wahyu Dhyanita Abhisekha Puspa Riyanda; Aloysius Soesilo (Psycho Idea, 2018)
Low socioeconomic status (SES) is one of the most common occurring problems  today. This kind of adversity may have serious impacts on societies, especially on only children who live with their single parent. The impacts may occur in several aspects such as parenting, child education and behavior and other psychological problems.This study intends  tofirst identifiy the difficulties and problems that the only  child with a single parent in low income and social status faces and to describe the adaptive processes within this significant adversity. This qualitative research uses a phenomenological approach. The data is collected through in-depth interviews and observations. The research participants are two children, each as an only child (one female, 14 years old, and one male, 18 years old), not married, and each of them hasa single parent with low socio economic status. The result of this study has shown both participants are adversely affected by their lack of affection and attention from their parents. They are not able to get possessions like their peers do.The limited role the single parent does and the low SES have affected the parenting styles  and the attitude and self-control of the children under in difficult situations. Resilience of both participants apparently differs in their adaptation within these significant adversities and in their orientation about education and career. Keyword : Resilience, Only Child, Single Parent, Low Socioeconomic Status